EVALUASI PENGELOLAAN SUMBER DAYA HUTAN BERSAMA MASYARAKAT (PHBM) DI KESATUAN PEMANGKUAN HUTAN (KPH) SEMARANG (STUDI DI LMDH SUMBER REJEKI) - Cendrasari, Khairunnisa; Subowo, Ari (Journal of Public Policy and Management Review, 2016)
Collaboration Forest Resource Management (PHBM) is a system of forest management conducted jointly by Perum Perhutani and forest village communities with interested parties (stakeholders) with the spirit of sharing that common interest to achieve sustainability of the functions and benefits of forest resources can be realized optimally and the improvement of the Human Development Index (HDI) which is flexible, adaptive, participatory, and accommodating PHBM as one form of social forestry is done to achieve sustainable forestry and forest communities prosper. However, the losses suffered due to illegal logging in the KPH Semarang is still high and has not decreased. Therefore, evaluation of which examines patterns in KPH Semarang management and the impact of PHBM for the forest village communities. This study focused on one LMDH namely LMDH Rejeki as a criterion independently LMDH. This study uses research methods qualitative descriptive. Data in this study were obtained from interviews with informants, observation and documents. The results of this study indicate that evaluation of Collaboration Forest Resource Management (PHBM) in KPH Semarang especially LMDH Rejeki has a management scheme implemented fairly well and in accordance with the conditions and the social dynamics of the community. Although there are still obstacles that are destroying the forests and their elements are decimating pohon.Forest Resource Management with Community has given the social and economic impact on society Kalikurmo Village of increased education, health, and positively impact the purchasing power masyarakat. Besides the positive effects , there are also some which impacts arising rift between Perum Perhutani officers with Kalikurmo Village community, institutional vacuum LMDH Rejeki, and lack of capital to develop productive enterprises.